2017
DOI: 10.1038/s41598-017-17724-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and metabolome profiling of Narcissus pseudonarcissus ‘King Alfred’ reveal components of Amaryllidaceae alkaloid metabolism

Abstract: Amaryllidaceae alkaloids (AAs) represent a diverse class of plant specialized metabolites and many display potent pharmacological activities. The AA metabolic pathway is poorly understood and resources are minimal. To enable AA pathway elucidation and novel biosynthetic enzymes discovery, we generated comprehensive metabolomic and corresponding transcriptomic datasets from different tissues of Narcissus pseudonarcissus ‘King Alfred’. In this study, we performed untargeted UPLC-QTOF-MS metabolite analysis from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 70 publications
(54 reference statements)
5
56
0
Order By: Relevance
“…However, most genes have been obtained and identified using traditional study technology. Since transcriptome analysis has come to be regarded as a crucial way to study the expression level, structure and function of genes in order to revealing phenotypic traits, combined analysis of transcriptome and metabolome has increasingly become a popular and practical tool for the mining of new genes involved in various metabolic pathways [ 49 ]. In this study, metabolome data, coupled with transcriptome profiling, was carried out in a combined analysis for the discovery of genes involved in flavonoid biosynthesis, thus searching for useful information to illustrate phenomenon of red coloring in A. arguta fruit.…”
Section: Discussionmentioning
confidence: 99%
“…However, most genes have been obtained and identified using traditional study technology. Since transcriptome analysis has come to be regarded as a crucial way to study the expression level, structure and function of genes in order to revealing phenotypic traits, combined analysis of transcriptome and metabolome has increasingly become a popular and practical tool for the mining of new genes involved in various metabolic pathways [ 49 ]. In this study, metabolome data, coupled with transcriptome profiling, was carried out in a combined analysis for the discovery of genes involved in flavonoid biosynthesis, thus searching for useful information to illustrate phenomenon of red coloring in A. arguta fruit.…”
Section: Discussionmentioning
confidence: 99%
“…Since transcriptome analysis is regarded as a central way to study the expression level, structure and function of genes to identify phenotypic traits, the combined analysis of both transcriptome and metabolome has increasingly become a popular and practical tool for the mining of new genes that may be involved in various metabolic pathways [48]. Thus, this method will likely become an effective tool that can be used to investigate the mechanisms involved in the regulation of the phenolic acid biosynthesis in C. paliurus.…”
Section: Discussionmentioning
confidence: 99%
“…The transcript expression analyses of the genes from the two clusters suggest a different functional role for PAL1 versus PAL2. It has been demonstrated that PAL1 is expressed at similar levels in all plant parts (root, bulb, stem, leaf, flower), whereas PAL2 is expressed in the bulb [ 59 , 65 , 66 ]. Another important gene from the phenylpropanoid pathway, cinnamate-4-hydroxylase (C4H), has been recently cloned and characterized to be present as a one single transcript in Amaryllidaceae alkaloid producing plants [ 59 , 60 , 64 , 65 , 67 ].…”
Section: Biotechnological Production Of Amaryllidaceae Alkaloidsmentioning
confidence: 99%
“…Another important gene from the phenylpropanoid pathway, cinnamate-4-hydroxylase (C4H), has been recently cloned and characterized to be present as a one single transcript in Amaryllidaceae alkaloid producing plants [ 59 , 60 , 64 , 65 , 67 ]. The transcript expression analyses of C4H showed that the expression was highest in the bulbs of dormant and early germination stages, and it was also high in the stems, roots and bulbs in flowering plants [ 59 , 64 , 65 , 66 ].…”
Section: Biotechnological Production Of Amaryllidaceae Alkaloidsmentioning
confidence: 99%
See 1 more Smart Citation